Challenge of History Teachers in Teaching and Learning Higher Order Thinking Skills (HOTS) (Paramita: Historical Studies Journal, 2020)
This study aims to identify the challenges faced by teachers and the efforts made in the implementation of HOTS-based history learning. In this study, a qualitative method was used by taking research at the Lab School in Kebayoran Jakarta. The analysis was carried using Strauss Corbin grounded theory approach. The results illustrate three interrelated things, namely the concept of HOTS used, implementation, and challenges faced by history teachers. This study shows that the difficulty faced by history teachers in teaching and learning history based on HOTS is that assessment has been carried out using the HOTS model. On the other hand, training in learning that supports HOTS has not been provided to teachers, many curriculum demands, teacher competencies/skills, lack of time in the learning process, and the learning design made by the teacher does not yet support HOTS. The efforts to answer these challenge can be overcome by (1) increasing teacher understanding/mastery of HOTS concepts, (2) the planning of learning devices arranged to suit the needs of students, and (3) during the implementation of learning using models that support HOTS namely inquiry learning.Penelitian ini bertujuan untuk mengidentifikasi tantangan yang dihadapi guru dan upaya yang dilakukan dalam pelaksanaan pembelajaran sejarah berbasis HOTS. Dalam penelitian ini, metode kualitatif digunakan dengan mengambil penelitian di SMA Lab School Kebayoran Jakarta. Analisis dilakukan dengan menggunakan pendekatan teori ground Strauss Corbin. Hasil penelitian menggambarkan tiga hal yang saling terkait, yaitu konsep HOTS yang digunakan, implementasi, dan tantangan yang dihadapi oleh guru sejarah. Studi ini menunjukkan bahwa kesulitan yang dihadapi oleh guru sejarah dalam pengajaran dan pembelajaran sejarah berdasarkan HOTS adalah penilaian telah dilakukan dengan menggunakan model HOTS. Di sisi lain, pelatihan dalam pembelajaran yang mendukung HOTS belum diberikan kepada guru, banyak tuntutan kurikulum, kompetensi / keterampilan guru, kurangnya waktu dalam proses pembelajaran, dan desain pembelajaran yang dibuat oleh guru belum mendukung HOTS. Upaya menjawab tantangan ini dapat diatasi dengan (1) peningkatan pemahaman guru / penguasaan konsep HOTS, (2) perencanaan perangkat pembelajaran yang disesuaikan dengan kebutuhan siswa, dan (3) selama pelaksanaan pembelajaran menggunakan model yang mendukung HOTS yaitu pembelajaran inkuiri.